The factors that influence customer preferences to choose Celcom Axiata as network provider in Kota Bharu Kelantan / Mat Zulazwan Abdul Malik - Abdul Malik, Mat Zulazwan (Universiti Teknologi MARA Cawangan Kelantan, 2014)
The purpose of this study is to identify the the factors that influence customer preferences to choose Celcom Axiata as network provider in Kota Bharu, Kelantan. There are there factors that being studied, which were: price offered, customer services and network quality. For data collection, the researcher used both the primary and secondary data. In addition, the questionnaires had been used to get feedback from customers. There were 150 set of questionnaire has been distributed to respondent. When the data was collected and tested on its reliability, then analyzed by using frequency analysis, descriptive mean tests and regression analysis. Lastly, the finding of this research is there are two independent variables which are price offered and network quality for collaration test. For reliability test, all independent variables are very good and dependent variable is very excellent